Tradisi Berobat Kampung pada Bulan Muharam, di Dusun Kalang Bahu 1950-2023 Desa Jawai Laut Kecamatan Jawai Selatan Kabupaten Sambas - Irena Privalopa; Beti Yanuri Posha; Sunandar Sunandar; Tomi Tomi (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
This research aims to reveal the history and changes in the implementation procession in the village medical tradition during the month of Muharram, in Kalang Bahu Hamlet, Jawai Laut Village, South Jawai District. The research method used is the historical research method and consists of the following elements; heuristics (data collection); verification (source criticism); interpretation (interpretation of sources); and historiography (writing). The results of the research show that the village medical tradition is a religious tradition, an expression of gratitude for the blessings that God has bestowed upon us, and a tradition of asking God for help to always provide safety and keep us away from danger. The village medical tradition in Kalang Bahu Hamlet underwent a process of change so that it was divided into three periods, the first period 1950-1973, the second period 1973-1983, and the third period 1983-Present. The changes that occur in village medical traditions are caused by the increasing development of people's understanding of religious teachings. Apart from that, the village medical tradition has values ​​contained in it such as religious values, mutual cooperation, solidarity and tolerance.